Sleeping sickness in Kenya - Sindiga, Isaac (ERDKUNDE, 1987)
In tropical Africa, trypanosomiasis (sleeping sickness in humans, Nagana epidemic in cattle) is of great economic importance, as this disease has more or less severely hampered the economic development of almost 10 million km² and thus about a third of the continent. Using the example of South Nyanza, Kenya, the following study documents the efforts made over the past decades to contain trypanosomiasis in humans and animals. After sleeping sickness first broke out in the study area in 1902, attempts were initially made to eradicate the carrier of the disease, the tsetse fly, and to provide medical care for the infected people. The habitat of the tsetse fly has been reduced by the clearing of bush vegetation and the creation of strips of open land around settlements. However, these measures were not very successful because the low population density and thus the lack of workers for the necessary clearing favored a reappearance of trees and effective remedies were missing. Even the increased use of insecticides to combat tsetse since the 1950s has not led to the definitive eradication of the disease to date. This is apparently due to the remarkable ability of the tsetse fly to adapt to changing environmental conditions. In addition, the establishment of a national park and a forest reserve in the study area has contributed to the preservation of suitable habitats for the tsetse fly and the pathogen, the trypanosomes. The sleeping sickness problem in southern Nyanza is shaped by the conflict between the conservation of natural resources and the demands of socioeconomic development. An effective solution to this conflict must take into account the entire epidemiological complex of sleeping sickness.